ESG Reporting: Assessing Compliance of Polish Public Companies with EU Taxonomy Guidelines - Koszel, Maciej (Zielona Góra: Faculty of Economics and Management Press)
The paper aims to evaluate how well Polish public companies` activities align with the European Union Taxonomy guidelines (EU Taxonomy). The research involved a review of literature on ESG and non-financial reporting, identification of key guidelines for mandatory disclosures, and analysis of reports from companies listed on the Warsaw Stock Exchange`s three main indices. This approach allowed for determining the shares of activities that meet the EU Taxonomy`s compliance and eligibility criteria, focusing on turnover, capital expenditures (CapEx), and operating expenditures (OpEx).
Keywords: ESG; public companies; EU Taxonomy; non-financial disclosure